Pengaruh Tingkat Suku Bunga, Inflasi, dan Indeks Dow Jones terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia - Prahasti, Rahma Amirah; Mahsuni, Abdul Wahid; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2023)
The progress of the capital market in Indonesia is supported by the need for capital which shows an increasing amount. The development of the capital market can be identified and observed from the fluctuations in the Jakarta Composite Index (IHSG) on the Indonesia Stock Exchange. Stock prices that are constantly changing will also affect the Jakarta Composite Index (IHSG). The movement of the Composite Stock Price Index (IHSG) can be influenced by several factors, such as macroeconomic factors including interest rates, inflation and there is also a foreign index, namely the Dow Jones index. Due to the weaknesses of previous research, this study aims to conduct further research on the effect of Interest Rates, Inflation and the Dow Jones Index on the JCI on the IDX in 2015-2019. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and testing the partial hypothesis (Test t). The results of this study indicate that the variable Interest Rate and Inflation have a negative and significant influence on the JCI, while the Dow Jones Index has a positive and significant influence on the JCI.Keywords: BI rate, inflation, the dow jones index, and the combined stock price index.